Bordeaux of Talca and Champagne of Mendoza: Appellations of Origin and identity contamination of wines in Argentina and Chile - Lacoste, Pablo Alberto; Jiménez Cabrera, Diego Ignacio; Briones Quiroz, Félix Maximiano; Castro San Carlos, Amalia; Rendón Zapata, Bibiana Marcela; Jeffs Munizaga, José Gabriel (Centro de Historia Argentina y Americana, 2014)
The development of Appellations of Origin (AO) is one of the wines of outstanding wine industry in Argentina and Chile subjects. Given the strong trend towards concentration of the wine industry in these two countries, it is relevant to study the AO because they represent an appropriate mechanism to reduce the gap and enhance the possibilities of SMEs. Why AO not have developed in Argentina and Chile? This article examines the causes that inhibit the development of local AO in the regional viticulture.